NILAI-NILAI PENDIDIKAN ISLAM : (Analisis Buku Misteri Banjir Nabi Nuh Karya Yosep Rafiqi) - Nurul Indana; Noor Fatikah; Amina Ba’dho (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
Yosep Rafiki's work on the mysterious story of Nuh flood is not just a reading, it contains educational values ??that are useful to human life, both individually and as a community. In the mysterious story of the flood Noah described the state of society and the soul of a living being in a time and place of trial and trial. In this study using library research, the results found are: Faith values, Commandments affirming Allah SWT, Commandments to believe in Allah and His Messenger, preaching to Allah and His Messenger, believing in the day of retribution. Worship Value: Performing the order amar ma'ruf nahi munkar to others including his people to invoke a straightforward course of faith in Allah Almighty. Moral Values: Be gentle in preaching, be polite, compassionate and advise each other, be patient, Prohibition to be arrogant, and prohibit no respect for others.